Friction reduction through biologically inspired scale-like laser surface textures - Schneider, Johannes; Djamiykov, Vergil; Greiner, Christian (Beilstein Journal of Nanotechnology, 2018)
Reducing friction forces is a major challenge in many engineering applications involving moving parts. For the past 50 years, the morphological texturing of surfaces for improving tribological properties has been investigated. Only recently, the application of biologically inspired surface features, like scales found on lizards and snakes, has come to the attention of tribologists. Here, we present results of the lubricated and unlubricated performance of biologically inspired scale-like textures applied with laser light to the surface of bearing steel pins. These were paired in unidirectional sliding against metallic (100Cr6), polymeric (PEEK) and ceramic (Al2O3) counter bodies. Additionally, a possible size effect was investigated by changing the scale diameter between 13 and 150 µm under dry sliding contact against sapphire. Our results demonstrate that depending on the contact conditions a biologically inspired surface morphology has the potential to reduce friction forces by more than 80%. However, under certain conditions, especially for slow-moving lubricated steel-on-steel and steel-on-ceramic contacts, these surface morphologies may increase friction as well. Similar to classical laser surface textures, such as round dimples, these biologically inspired morphologies need to be carefully optimized for each tribological system in which they are intended to be applied. There is no standard solution for all sliding conditions. The results presented here demonstrate that such efforts have the potential to yield significant reduction in friction forces and are expected to spark future research in the field of biologically inspired surface morphologies applied to tribological contacts.
Keywords: bioinspiration; friction; laser surface texturing; scales; tribology

(untitled) - Holmberg, K.; Erdemir, A. (Friction, 2017)

(untitled) - Tung, S. C.; McMillan, M. L. (Tribol. Int., 2004)

(untitled) - Nicholls, M. A.; Do, T.; Norton, P. R.; Kasrai, M.; Bancroft, G. M. (Tribol. Int., 2005)

Surface Coatings for Advanced Materials - Bull, S. J. (Tribological and micro-tribological phenomena in coatings, 1997)

(untitled) - Erdemir, A.; Donnet, C. (J. Phys. D: Appl. Phys., 2006)

(untitled) - Holmberg, K.; Ronkainen, H.; Matthews, A. (Ceram. Int., 2000)

(untitled) - Sawyer, W. G.; Argibay, N.; Burris, D. L.; Krick, B. A. (Annu. Rev. Mater. Res., 2014)

(untitled) - Greiner, C.; Liu, Z.; Strassberger, L.; Gumbsch, P. (ACS Appl. Mater. Interfaces, 2016)

(untitled) - Wolff, K.; Liu, Z.; Braun, D.; Schneider, J.; Greiner, C. (Tribol. Int., 2016)

State of the Art in Laser Surface Texturing - Etsion, I. (Tsinghua University Press, 2009)

(untitled) - Anno, J. N.; Walowit, J. A.; Allen, C. M. (J. Lubr. Technol., 1968)

(untitled) - Costa, H. L.; Hutchings, I. M. (J. Mater. Process. Technol., 2009)

(untitled) - Pettersson, U.; Jacobson, S. (Tribol. Int., 2006)

(untitled) - Gachot, C.; Rosenkranz, A.; Hsu, S. M.; Costa, H. L. (Wear, 2017)

(untitled) - Braun, D.; Greiner, C.; Schneider, J.; Gumbsch, P. (Tribol. Int., 2014)

(untitled) - Schneider, J.; Braun, D.; Greiner, C. (Lubricants, 2017)

(untitled) - Abdel-Aal, H. A. (Surf. Topogr.: Metrol. Prop., 2016)

(untitled) - Grewal, H. S.; Pendyala, P.; Shin, H.; Cho, I.-J.; Yoon, E.-S. (Wear, 2017)

(untitled) - Zhang, Z.; Shao, F.; Liang, Y.; Lin, P.; Tong, X.; Ren, L. (J. Mater. Eng. Perform., 2017)

(untitled) - Zhang, J.; Chen, W.; Yang, M.; Chen, S.; Zhu, B.; Niu, S.; Han, Z.; Wang, H. (Tribol. Lett., 2017)

(untitled) - Baum, M. J.; Heepe, L.; Gorb, S. N. (Beilstein J. Nanotechnol., 2014)

(untitled) - Baum, M. J.; Heepe, L.; Fadeeva, E.; Gorb, S. N. (Beilstein J. Nanotechnol., 2014)

(untitled) - Greiner, C.; Schäfer, M. (Bioinspiration Biomimetics, 2015)

(untitled) - Cuervo, P.; López, D. A.; Cano, J. P.; Sánchez, J. C.; Rudas, S.; Estupiñán, H.; Toro, A.; Abdel-Aal, H. A. (Surf. Topogr.: Metrol. Prop., 2016)

(untitled) - Baumgartner, W.; Saxe, F.; Weth, A.; Hajas, D.; Sigumonrong, D.; Emmerlich, J.; Singheiser, M.; Böhme, W.; Schneider, J. M. (J. Bionic Eng., 2007)

(untitled) - Singh, R. A.; Yoon, E.-S. (J. Korean Phys. Soc., 2008)

(untitled) - Greiner, C.; Merz, T.; Braun, D.; Codrignani, A.; Magagnato, F. (Surf. Topogr.: Metrol. Prop., 2015)

(untitled) - Greiner, C.; Schäfer, M.; Popp, U.; Gumbsch, P. (ACS Appl. Mater. Interfaces, 2014)

(untitled) - Blau, P. J. (Tribol. Int., 2005)

(untitled) - Blau, P. J. (J. Mater. Eng., 1991)

(untitled) - Scherge, M. (Lubricants, 2018)

(untitled) - Linsler, D.; Schröckert, F.; Scherge, M. (Tribol. Int., 2016)

(untitled) - Brink, A.; Lichtenberg, K.; Scherge, M. (Wear, 2016)

(untitled) - Emge, A.; Karthikeyan, S.; Kim, H. J.; Rigney, D. A. (Wear, 2007)

(untitled) - Zum Gahr, K.-H.; Wahl, R.; Wauthier, K. (Wear, 2009)

(untitled) - Zum Gahr, K. H.; Mathieu, M.; Brylka, B. (Wear, 2007)

(untitled) - Wöppermann, M.; Zum Gahr, K.-H.; Schneider, J. (Tribol. Schmierungstech., 2010)

(untitled) - Arzt, E. (Acta Mater., 1998)

(untitled) - Arzt, E.; Gorb, S.; Spolenak, R. (Proc. Natl. Acad. Sci. U. S. A., 2003)

(untitled) - Greiner, C.; del Campo, A.; Arzt, E. (Langmuir, 2007)

(untitled) - Greiner, C.; Buhl, S.; del Campo, A.; Arzt, E. (J. Adhes., 2009)

(untitled) - Hamilton, G. M. (Proc. Inst. Mech. Eng., Part C, 1983)

(untitled) - Hertz, H. (J. Reine Angew. Math., 1882)

(untitled) - Pastewka, P. L.

(untitled) - Boesel, L. F.; Greiner, C.; Arzt, E.; del Campo, A. (Adv. Mater., 2010)

(untitled) - Varenberg, M.; Halperin, G.; Etsion, I. (Wear, 2002)

(untitled) - Ma, C.; Bai, S.; Peng, X.; Meng, Y. (Appl. Surf. Sci., 2013)

(untitled) - Lu, X.; Khonsari, M. M. (Tribol. Lett., 2007)

(untitled) - Fowell, M.; Olver, A. V.; Gosman, A. D.; Spikes, H. A.; Pegg, I. (J. Tribol., 2007)

(untitled) - Codrignani, A.; Frohnapfel, B.; Magagnato, F.; Schreiber, P.; Schneider, J.; Gumbsch, P. (Tribol. Int., 2018)

The Friction and Lubrication of Solids - Bowden, F. P.; Tabor, D. (Clarendon Press, 1950)

(untitled) - Rigney, D. A.; Karthikeyan, S. (Tribol. Lett., 2010)

(untitled) - Greiner, C.; Liu, Z.; Schneider, R.; Pastewka, L.; Gumbsch, P. (Scr. Mater., 2018)

(untitled) - Liu, Z.; Patzig, C.; Selle, S.; Höche, T.; Gumbsch, P.; Greiner, C. (Scr. Mater., 2018)

(untitled) - Filippov, A.; Gorb, S. N. (Sci. Rep., 2013)

(untitled) - Filippov, A. E.; Gorb, S. N. (Sci. Rep., 2016)

(untitled) - Singh, R. A.; Pham, D.-C.; Kim, J.; Yang, S.; Yoon, E.-S. (Appl. Surf. Sci., 2009)

(untitled) - Singh, R. A.; Yoon, E.-S. (Wear, 2007)

(untitled) - Resendiz, J.; Graham, E.; Egberts, P.; Park, S. S. (Tribol. Int., 2015)

(untitled) - Klein, M.-C. G.; Deuschle, J. K.; Gorb, S. N. (J. Comp. Physiol., A, 2010)

(untitled) - Klein, M.-C. G.; Gorb, S. N. (J. R. Soc., Interface, 2012)

(untitled) - Stribeck, R. Z. (Z. Ver. Dtsch. Ing., 1902)

(untitled) - Abdel-Aal, H. A.; Vargiolu, R.; Zahouani, H.; El Mansori, M. (Wear, 2012)